Evaluation of the role and significance of cryptocurrencies in developing economies - Stamenic, Pavle; Slaný, Martin, 1982-; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
With the publishing of Bitcoin in 2009 it introduced the world to the new technology that are cryptocurrencies, presenting new opportunities for developed and developing countries. Our study investigates whether financial barriers such as accessibility to financial institutions and economic freedom measures affect the usage of bitcoin in developing economies. The analysis was carried out by panel regression using the random effect method to determine whether lacking financial and economic infrastructure had an effect on the usage of bitcoin for the years 2014-2019. Comparisons and implementations of various panel regressions have been applied to determine the most viable analysis for our study, as well as the Wooldridge test for autocorrelation. Our results suggest that there is indeed an effect of financial barriers and economic freedom on the usage of bitcoin, showing greater usage as access to financial institutions decreases and an increase in usage with greater economic freedom measures. This research can provide implications for the adoption of cryptocurrencies in developing countries and highlight to governments where their financial infrastructure is lacking.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses